(untitled) (Stamford Journal of Pharmaceutical Sciences, 2011)
Key words: Carbon tetrachloride; Silymarin; Solena amplexicaulis; hepatoprotective activity; biochemical parameter DOI: http://dx.doi.org/10.3329/sjps.v3i2.5953 S.J. Pharm. Sci 3(2): 01-06